O14. Inter-observer variation of prostate delineation on CT and MR: A multidisciplinary study. (September 2016) - Strauss, L.; Chabane, W.; Sherriff, A.; Loots, C.
Abstract : Introduction: At our clinic a significant proportion of prostate cancer patients are treated with curative radiation therapy, and targets are defined through manual delineation. In this study we evaluate the variation of prostate delineation between radiation oncologists, radiologists and urologists respectively on CT and MR images. Materials and methods: CT and MR image sets of 5 prostate cancer patients were presented separately for prostate delineation in a blinded and independent fashion to specialists from various hospitals: 7 radiation oncologists, 6 oncology registrars, 6 radiologists, and 3 urologists. Variations were first analysed visually. In-house tools were developed to automatically analyse various metrics including volume, positions of the base and apex, Conformity Index (CI), Maximum Volume Ratio (MVR), and a new metric, the volume centroids. Results: Significant differences were seen between individuals and groups. Volumes for the prostate differed between oncologists by 19.6% with a CI of 0.31, and for the other specialists by 15.9% and CI of 0.38. Volumes were significantly larger on CT than the corresponding MR image sets in all cases, with a MVR for oncologists of 2.23 ± 0.9 and for the other specialists of 1.52 ± 0.39. Variations in the base position were less than 3 slices but for the apex positions up to 7 slices, and varied more on CT than MR. The volume centroids provided useful interpretation of the spread in 3 dimensions. Conclusion: The new tools provided valuable insight and information. Large inter-observer differences were found and areas of disagreements identified. MR images proved to be critical when delineating the prostate. Clear protocols and guidelines are thus essential to ensure delineation consistency within a department. The urologists produced the most comparable delineations, followed by the radiologists and lastly the oncologists. This has already urged further investment in the delineation skills of the oncologists.